Microduplications encompassing the Sonic hedgehog limb enhancer ZRS are associated with Haas‐type polysyndactyly and Laurin‐Sandrow syndrome. (17th February 2014) - Lohan, S.; Spielmann, M.; Doelken, S.C.; Flöttmann, R.; Muhammad, F.; Baig, S.M.; Wajid, M.; Hülsemann, W.; Habenicht, R.; Kjaer, K.W.; Patil, S.J.; Girisha, K.M.; et al.
<x xml:space="preserve">Abstract</x> Laurin‐Sandrow syndrome (LSS) is a rare autosomal dominant disorder characterized by polysyndactyly of hands and/or feet, mirror image duplication of the feet, nasal defects, and loss of identity between fibula and tibia. The genetic basis of LSS is currently unknown. LSS shows phenotypic overlap with Haas‐type polysyndactyly (HTS) regarding the digital phenotype. Here we report on five unrelated families with overlapping microduplications encompassing the Sonic hedgehog (SHH) limb enhancer ZPA regulatory sequence (ZRS) on chromosome 7q36. Clinically, the patients show polysyndactyly phenotypes and various types of lower limb malformations ranging from syndactyly to mirror image polydactyly with duplications of the fibulae. We show that larger duplications of the ZRS region (>80 kb) are associated with HTS, whereas smaller duplications (<80 kb) result in the LSS phenotype. On the basis of our data, the latter can be clearly distinguished from HTS by the presence of mirror image polysyndactyly of the feet with duplication of the fibula. Our results expand the clinical phenotype of the ZRS‐associated syndromes and suggest that smaller duplications (<80 kb) are associated with a more severe phenotype. In addition, we show that these small microduplications within the ZRS region are the underlying genetic cause of Laurin‐Sandrow syndrome.